Boston type I keratoprosthesis-donor cornea interface evaluated by high-definition spectral-domain anterior segment optical coherence tomography - Alzaga Fernandez AG (Dove Medical Press, 2012)
Ana G Alzaga Fernandez,* Nathan M Radcliffe,* Kimberly C Sippel, Mark I Rosenblatt, Priyanka Sood, Christopher E Starr, Jessica B Ciralsky, Donald J D'Amico, Szilárd KissDepartment of Ophthalmology, Weill Cornell Medical College, New York-Presbyterian Hospital, New York, NY, USA*These authors contributed equally to this work and both are considered principal authorsBackground: The purpose of this study was to assess whether the resolution offered by two different, recently commercially available high-resolution, spectral-domain anterior segment optical coherence tomography (AS-OCT) instruments allows for detailed anatomic characterization of the critical device-donor cornea interface in eyes implanted with the Boston type I permanent keratoprosthesis.Methods: Eighteen eyes of 17 patients implanted with the Boston type I keratoprosthesis were included in this retrospective case series. All eyes were quantitatively evaluated using the Cirrus HD-OCT while a subset (five eyes) was also qualitatively imaged using the Spectralis Anterior Segment Module. Images from these instruments were analyzed for evidence of epithelial migration onto the anterior surface of the keratoprosthesis front plate, and presence of a vertical gap between the posterior surface of the front plate and the underlying carrier donor corneal tissue. Quantitative data was obtained utilizing the caliper function on the Cirrus HD-OCT.Results: The mean duration between AS-OCT imaging and keratoprosthesis placement was 29 months. As assessed by the Cirrus HD-OCT, 83% of eyes exhibited epithelial migration over the edge of the front plate. Fifty-six percent of the keratoprosthesis devices displayed good apposition of the device with the carrier corneal donor tissue. When a vertical gap was present (44% of eyes), the mean gap was 40 (range 8–104) microns. The Spectralis Anterior Segment Module also displayed sufficient resolution to allow for similar characterization of the device-donor cornea interface.Conclusion: Spectral-domain AS-OCT permits high resolution imaging of the keratoprosthesis device-donor cornea interface. Both the Cirrus HD-OCT and the Spectralis Anterior Segment module allowed for visualization of epithelial coverage of the device-donor cornea interface, as well as identification of physical gaps. These imaging modalities, by yielding information in regard to integration of the keratoprosthesis with surrounding corneal tissue, may help identify those at risk for keratoprosthesis-related complications, such as extrusion and endophthalmitis, and hence guide clinical management.Keywords: keratoprosthesis, anterior segment optical coherence tomography, epithelialization